“Aku Berharga”: A Psychoeducational Program to Improve Elementary Students’ Self-Esteem - Fransisca Iriani Roesmala Dewi; Salsa Hanifah Maryam; Safa Canina Ibrahim; Jessica Elisabeth; Hana Putri Chandra; Awrel Nindya Margaretha (Universitas AMIKOM Yogyakarta, 2026)
Low self-esteem in elementary school students may affect confidence, classroom participation, and social interaction during the learning process. This community service program aimed to improve the self-esteem of fourth-grade students at SDN Maleber through psychoeducation and interactive activities. The program was conducted over three days involving 22 students. The implementation stages included initial observation, pre-test administration, psychoeducation sessions, group games, positive affirmation activities, self-reflection, interactive discussions, and post-test evaluation using the Rosenberg Self-Esteem Scale (RSES). The instrument demonstrated good reliability with a Cronbach’s alpha value of 0.784. Descriptive analysis showed an increase in the average self-esteem score from 25.32 before the intervention to 28.55 after the intervention. Data analysis using the Wilcoxon Signed-Rank Test showed a significant increase in students’ self-esteem after participating in the program (p = 0.004). In addition, students appeared more confident, active, and willing to express their opinions during classroom activities. These findings indicate that psychoeducation and participatory activities can positively support the development of self-esteem among elementary school students.